Uji Daya Tolak Lilin Aromaterapi Minyak Atsiri Serai (Cymbopogon citratus) terhadap Nyamuk Aedes aegypti - Anizah Paramitha Dewi; Novyan Lusiyana (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2020)
Aromatherapy candle is a safe, effective, and cost-effective repellent. It has a potential repellent effect particularly on mosquitoes. Lemongrass is a potential plant as a natural repellent for Aedes aegypti. The purpose of this study was to determine the repellency effect of lemongrass essential oils against Ae. aegypti. This study was an experimental study with a post-test only with control group design, which was divided into six groups (one negative control and five treatment groups 9%, 10%, 11%, 12%, and 13%) with four repeats. Each group consisted of 20 Ae. aegypti female mosquitoes, so the total number of mosquitoes used was 480. Tested mosquitos were exposed to aromatherapy candles for one hour, and their repellency observed every 15-minute intervals. The average of repellency effect of the negative control and 5 treatment groups at minute 60 were 7.5%; 0%; 33.33%; 66.67%; 66.67%; and 100% respectively. We conclude that the aromatherapy candle of lemongrass essential oil was effective as a 100% repellency effect against Ae. aegypti at a concentration of 13%.